DISTRACTERS OF MOTIVATION IN PRODUCING A WRITTEN TEXT OF STUDENTS IN EFL CLASSROOM - Salieva , Ziroat Zokirovna (Educational Research in Universal Sciences, 2024)
The transition to writing in academic English is one of the many difficulties Uzbek students at Uzbekistan universities face. Expectations have changed significantly, reflecting both a linguistic and cultural shift. It is thought that writing is a challenging skill for students to acquire. Many students struggle because they have to consider both the content and the syntactic structure of the second language when they are required to express themselves in writing. The majority of students will not be aware of the conventional essay format or the significance of a well-defined thesis statement. Because of this, educators ought to assist in identifying the obstacles to writing in order to increase students’ motivation to write.